110k views
3 votes
Which would not be sufficient to prove triangle WXZ - triangle WYX.

Which would not be sufficient to prove triangle WXZ - triangle WYX.-example-1

1 Answer

3 votes

ANSWER:


B)(WX)/(WZ)=(XZ)/(ZX)

Given the triangle, the eqution that would not be sufficient enough to prove that WXZ = WYZ is:


B)(WX)/(WZ)=(XZ)/(ZX)

From the triangle to prove that WXZ is similar to WYX, let's seperate both triangles

From the above, we can see that from both triangles, we have:

WZ = XW

WX = YW

∠WXZ = WYX

XZ = WX

Which would not be sufficient to prove triangle WXZ - triangle WYX.-example-1
User Matthias Hryniszak
by
6.3k points